Induction of Reactive Oxygen Species Is Necessary for Efficient Onset of Cyprinid Herpesvirus 2 Replication: Implications for Novel Antiviral Strategy With Antioxidants - Lu, Cuiyu; Tang, Ruizhe; Su, Meizhen; Zou, Jixing; Lu, Liqun (Frontiers in Microbiology, 2022)
Cyprinid herpesvirus 2 (CyHV-2) has caused great economic loss to Crucian carp breeding industry. Upon viral stimulation, eukaryotic cells generally activate the expression of anti-oxidative genes to maintain the intracellular oxidative balance and resist viral infection. Here, intracellular reactive oxygen species (ROS) levels in CyHV-2 infected cells were monitored to show that CyHV-2 induced the increase of intracellular ROS during early infection, and intracellular excessive accumulation of ROS was ameliorated during late infection, which was accompanied by activated expression of genes related to Nrf2 signaling pathway. In order to explore the interaction between CyHV-2 infection and ROS production, RyuF-2 cells were treated with antioxidant EGCG (Epigallocatechin-3-gallate) or BBH (Berberine Hydrochloride), and then infected with CyHV-2. Our results indicated that both BBH and EGCG could effectively inhibit the amplification of CYHV-2. Consisted with this, the oxidant stress-related genes were up-regulated by CyHV-2 infection and the production of ROS was inhibited in cells treated with either BBH or EGCG through modulating virus-induced ROS accumulation. These results demonstrated that early ROS accumulation favored the replication of CyHV-2; while, antioxidants (BBH and EGCG) could inhibit the amplification of CyHV-2 by inhibiting ROS induction.